Numerical studies on the link between radioisotopic signatures on earth and the formation of the local bubble: I. 60Fe transport to the solar system by turbulent mixing of ejecta from nearby supernovae into a locally homogeneous interstellar medium - Schulreich, Michael Mathias; Dettbarn, Christian (Astronomy and astrophysics, 2017)
Context. The discovery of radionuclides like 60Fe with half-lives of million years in deep-sea crusts and sediments offers the unique possibility to date and locate nearby supernovae.Aims. We want to quantitatively establish that the 60Fe enhancement is the result of several supernovae which are also responsible for the formation of the Local Bubble, our Galactic habitat.Methods. We performed three-dimensional hydrodynamic adaptive mesh refinement simulations (with resolutions down to subparsec scale) of the Local Bubble and the neighbouring Loop I superbubble in different homogeneous, self-gravitating environments. For setting up the Local and Loop I superbubble, we took into account the time sequence and locations of the generating core-collapse supernova explosions, which were derived from the mass spectrum of the perished members of certain stellar moving groups. The release of 60Fe and its subsequent turbulent mixing process inside the superbubble cavities was followed via passive scalars, where the yields of the decaying radioisotope were adjusted according to recent stellar evolution calculations.Results. The models are able to reproduce both the timing and the intensity of the 60Fe excess observed with rather high precision, provided that the external density does not exceed 0.3 cm-3 on average. Thus the two best-fit models presented here were obtained with background media mimicking the classical warm ionised and warm neutral medium. We also found that 60Fe (which is condensed onto dust grains) can be delivered to Earth via two physical mechanisms: either through individual fast-paced supernova blast waves, which cross the Earth’s orbit sometimes even twice as a result of reflection from the Local Bubble’s outer shell, or, alternatively, through the supershell of the Local Bubble itself, injecting the 60Fe content of all previous supernovae at once, but over a longer time range.
Die 60 im Titel ist hochgestellt
Gesehen am 18.10.2017